EMPLOYMENT DISCRIMINATION BASED ON EMPLOYEE LIFESTYLES DRAFT REPORT FOR THE ACLU 910308 - SCHLOERB, JOHN (Tufts Archival Research Center, 2007)
Draft; Revised document that examines different types of employment discrimination based on employee lifestyle habits. Mentions different companies that hire and fire employees based on personal lifestyle behaviors such as smoking, obesity, cholesterol levels, etc. Adds that employers feel they must discriminate because of health insurance costs. Concludes that if this trend continues, more and more employees will be discriminated against.